Physiographic Study of Java Island Based on EMAG2 v3 Data: Studi Fisiografi Pulau Jawa Berdasarkan Data EMAG2 v3 - Yuniantari, Thava; Fikri Niyartama, Thaqibul; Zakaria, Muhammad Faizal; Rosyida, Hana (Sunan Kalijaga Journal of Physics, 2025)
This study aims to analyze the physiography of Java Island based on the Earth Magnetic Anomaly Grid version 3 (EMAG2 v3) satellite data. The EMAG2 v3 dataset represents a global magnetic anomaly compilation acquired from satellite measurements provided by the National Oceanic and Atmospheric Administration (NOAA). The magnetic method, a geophysical technique that utilizes variations in the Earth’s magnetic field anomalies, was employed to delineate subsurface geological structures. The datasets used include administrative maps, regional geological maps, physiographic maps, and magnetic anomaly maps derived from EMAG2 v3 processing. Data processing was performed using the Geosoft Oasis Montaj software to generate the magnetic anomaly map of Java Island. The results indicate that the magnetic anomaly values across Java Island range from −300 nT to 450 nT, showing spatial variations among different physiographic zones. The northern part of Java exhibits low to moderate magnetic anomalies that correlate with alluvial deposits and young sedimentary formations, while the southern part displays moderate to high anomalies, reflecting the presence of volcanic rocks and intrusive bodies. This analysis demonstrates a strong correlation between magnetic anomaly variations and the lithological as well as structural characteristics of each physiographic zone. Therefore, EMAG2 v3 data can be effectively utilized to comprehensively interpret the regional geological framework of Java Island.